With phases: how two wrongs can sometimes make a right - Roversi, P; Johnson, S; Lea, S (International Union of Crystallography, 2010)
In isolation, both weak isomorphous/anomalous difference signals from heavy-atom derivatization and phases from partial molecular-replacement solutions for a subset of the asymmetric unit often fall short of producing interpretable electron-density maps. Phases generated from very partial molecular-replacement models (if generated carefully) can be used to reliably locate heavy-atom sites, even if the signal is not sufficiently strong to allow robust finding of the sites using Patterson interpretation or direct methods. Additional advantages are that using molecular-replacement phases to define the heavy-atom substructure avoids the need for subsequent hand determination and/or origin-choice reconciliation and that the partial model can be used to aid the mask determination during solvent flattening. Two case studies are presented in which it was only by combining experimental and molecular-replacement phasing approaches that the crystal structures could be determined.